Copper and silver in medical devices - Miranda, Cristian; Castaño, Johanna (Base Diseño e Innovación, 2015)
The challenge of a research project at the University of Concepción is the design of a polymeric material that will eliminate the pathogenic bacteria that causes nocosomial pneumonia. Its base is the pvc with incorporated core-shell nanoparticles, where copper nanostructures will be coated with silver.